(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The health advantages of yoga are secular and real. Yoga has been practiced for thousands ofyears with the intention of bettering one’s physical health, mental health, and spiritual connection.Athletics is a catch-all term for any human-played competitive sport or game that requires physical skill,as well as the methods used to prepare athletes for those activities. Athletes take part in athletictournaments because they provide a human-centered, physical environment in which to evaluate factorslike stamina, fitness, and talent. Athletic competition is the norm, but interest in motor sports, precisionevents, and even animal sports is on the rise. The Ancient Olympic Games featured both horse andprehistoric athletic disciplines. The current word athletic derives from the Ancient Greek word (athios)for contest. Beginning in the late 19th century, organizations such as the Amateur Athletic Union in theUnited States and the Union des Societies Franchises de Sports Athletiques in France established formalframeworks for amateur sports. The National Collegiate Athletic Association (NCAA) was created in 1906to oversee the operations of the Intercollegiate Athletic Association of the United States, the governingbody for college sports in the United States. Talented athletes can now receive athletic scholarships toattend college and go on to represent their alma mater in a competitive athletic league, demonstratingthe increased importance academic institutions are placing on athletics. Since the Industrial Revolution,people in the developed world have been less physically active, making sports increasingly crucial totheir everyday lives. Athletes can gain access to gyms and other training facilities for a wide range ofsports and games at athletic clubs located all over the globe.